PENGARUH CONSUMER ATTITUDE DAN SUBJECTIVE NORM TERHADAP INTENTION TO BUY SAAT KRISIS MEREK - Gusti Belo Limbong; wiwid Noor Rakhmad (Interaksi Online, 2026)
This study analyzes the effect of consumer attitude and subjective norm on intention to buy Aqua products amid the water source crisis. Using a quantitative survey of 100 bottled water consumers and multiple linear regression, the results show that consumer attitude positively and significantly affects intention to buy (t = 9.657, sig < 0.001), as does subjective norm (t = 5.606, sig < 0.001). Simultaneously, both variables explain 66.8% of the variance in purchase intention (F = 97.569, R² = 0.668). These findings reinforce the Theory of Reasoned Action (TRA), with consumer attitude proving more dominant than subjective norm in the context of a brand reputation crisis.